Structure and performance of Na+ and Fe2+ co-doped Li1-xNaxMn0.8Fe0.2PO4/C nanocapsule synthesized by a simple solvothermal method for lithium ion batteries. Issue 8 (1st June 2019) - Li, Rong; Fan, Changling; Zhang, Weihua; Tan, Muchu; Zeng, Taotao; Han, Shaochang
Abstract: Na + and Fe 2+ were co-doped at the Li and Mn site of LiMnPO4 /C through a simple solvothermal method. Researches show that Li1-x Nax Mn0.8 Fe0.2 PO4 /C nanocapsule is generated through the self-assembly without surfactant. The simultaneous successfully doping of Na + and Fe 2+, which is proved by the EDS and XPS of Li0.97 Na0.03 Mn0.8 Fe0.2 PO4 /C (LN-3), does not cause the rearrangement of cation. The particle sizes of nanocapsule decrease gradually with the doping of Na + . The pyrolytic carbon with excellent conductivity is coated on the surface of nanocapsule. The crystal of LN-3 nanocapsule with regular diffraction lattice is well developed. The doping of Na + does not change the potential of electrochemical reaction. Cathode LN-3 delivers the maximum electrochemical performance. Its specific capacity at 0.05 C, 1 C and 5 C are improved to 141.7, 125.0 and 89.5 mAh·g −1, which is partially resulting from the enhanced diffusion coefficient of lithium ions. The capacity retention ratio in 200 cycles at 0.5 C is 96.65%. The ex-situ XRD patterns after 200 cycles are nearly unchanged and the structure is proved to be very stable. The doping of Na + can also inhibit the dissolution of Mn 2+ and Fe 2+ in the electrolyte.